THE AUTHENTICITY OF YOGA AS TOURIST SPECIAL INTEREST IN UBUD BALI - Putu Urip Wijaya; Warto Warto; Mahendra Wijaya (Proceeding of International Conference on Art, Language, and Culture, 2019)
This article focuses on the characteristics of authenticity concept of tourist attraction. The purpose of this research was to identify the concept of authenticity of yoga as one of the main tourist attractions in Ubud, Bali. Data was collected in Kundalini Tantra Yoga straight from Master Ketut Arsana at Om Ham Resort and Retreat. The interview resulted in several different perspectives of an authenticity of tourist attraction for the stakeholders such as the business owner, tourist itself and the surrounding people. Ubud as the yoga’s largest tourist attraction in Indonesia has influenced the raising number of visit to Bali especially to learn yoga. This phenomenon has encouraged people, both locals and foreigners, to be the yoga instructors due to the raising demand. This variety of yoga instructors offers a new concept because of the instructor diversity. Research findings: 1) There’s a resistant from foreign tourist who cannot experience the pure, unique and authentic yoga which covered in the local wisdom of Bali due to the shifting from local to foreign instructor 2) This is an unsolved issue for local yoga instructor demands coming from foreign tourist whilst the locals are still reluctant to fill the gap.